Are Health Institutions Involved In Health Care Induced Demand? (A Qualitative Study) - Mahmoud Keyvanara; Saeed Karimi; Elahe Khorasani; Marzie Jafarian Jazi (Tehran University of Medical Sciences, 2014)
Background and Aim: The hypothesis of supplier induced demand has attracted a lot of attention over the past three decades. Most studies in this field agree that healthcare providers have the ability to influence the demand for their products. The purpose of this study is to evaluate the role of institutions in the phenomenon of induced demand. This study has been done using experts' experiences in Isfahan University of Medical Sciences.  Materials and Methods: This is a qualitative study in which the semi-structured interview was used for data generation. The participants were those informed in this regard and considered as experts. For data saturation, purposive sampling was done. In this study, 17 people were interviewed, and criteria such as reliability and stability were considered. The anonymity of the interviewees was guaranteed. The data were transcribed and categorized, and then analyzed using thematic analysis.  Results: In the present study, thematic analysis was conducted and 30 sub-themes and 2 main themes were extracted. The two main themes were healthcare insurance organizations and other health organizations. Each of the themes had its own sub-themes.  Conclusion: The findings help health policy-makers have a better picture regarding the role of various institutions in the phenomenon of induced demand.